Obstacles to Using E-Learning in Teaching English for Students with Learning Disabilities during the Covid-19 Pandemic from Teachers' Point Of View - Mohmmad Ahmad Khasawneh (STAI Miftahul Ula Nganjuk, 2021)
This study aimed at identifying the obstacles to using e-learning in teaching English language to students with learning disabilities from the viewpoint of teachers in Jordan during the emerging Covid-19 pandemic. The study used the descriptive approach and developed a questionnaire consisting of (40) items and included four dimensions; obstacles related to school administration, obstacles related to school equipment, obstacles related to teachers, and obstacles related to students. The validity and reliability of the instrument were ensured and the instrument was applied to a sample of (200) teachers who were selected randomly. The results of the study showed that there are obstacles to the use of e-learning in teaching English to students with learning disabilities from the viewpoint of teachers in Jordan during the new Covid-19 pandemic. The results also revealed the presence of statistically significant differences in teachers’ responses related to e-learning obstacles attributable to the variables (gender and academic qualification). Based on the results, the researcher recommended providing communication while using the e-learning system and limiting its interruption.